1981
DOI: 10.1159/000176518
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Intake Reduction in Volunteer Families by Using a Salt Substitute and Nutrition Counselling

Abstract: A double-blind study on the home use of regular salt (RS) and a salt substitute, called Mineral Salt® (MS), was done in 58 volunteer families all with a 13-year-old child. All the salt used at home was replaced by one of the test salts for 4 months. After the first 2 months the parents were given a 5-hour course on reducing sodium intake by changing food habits. The test salt consumption was measured by weighing the leftover salt after 2 and 4 months. The parents and 13-year-old children collected 24-hour urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Avoiding adding salt during cooking and at the table were some of the more commonly reported actions taken by parents to help reduce salt use at home. Our findings are, therefore, indicative of the positive impact of educational messages on improving salt-related behaviors among families and are similar to a home-based salt reduction education program conducted in Finland [25]. In this Finnish study of 58 parents and their 13 year old children (n=58), 78% of parents reported reducing salt added to food prepared at home after a 5-hour course on reducing salt intake by changing food habits [25].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Avoiding adding salt during cooking and at the table were some of the more commonly reported actions taken by parents to help reduce salt use at home. Our findings are, therefore, indicative of the positive impact of educational messages on improving salt-related behaviors among families and are similar to a home-based salt reduction education program conducted in Finland [25]. In this Finnish study of 58 parents and their 13 year old children (n=58), 78% of parents reported reducing salt added to food prepared at home after a 5-hour course on reducing salt intake by changing food habits [25].…”
Section: Discussionsupporting
confidence: 81%
“…Parents have previously been included in school-based salt reduction education programs [24,25]. These interventions have demonstrated some improvements in children’s knowledge regarding salt and health and food label reading [24,25]; however, these studies were conducted over 30 years ago. To date, there have been no Web-based family education programs specifically targeting salt reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Fifteen (83%) were published between 1980 and 1990. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Measurement of Participant and Setting Characteristics Known to Influence Behavior…”
Section: Resultsmentioning
confidence: 99%
“…Participant age, ethnicity, and morbidity are correlated with variations in salt consumption 23 ; these factors influence how people learn and sustain habits of buying and salting food. Only 12 (66%) of the reviewed studies described participant age: one (6%) focused on older adults aged 76 to 100 years, 8 three (17%) focused on adolescents and children aged 6 to 15 years who were specifically assessed using clinical and recall methods, 9,24,25 two (11%) included all ages, 10,11 and six (33%) assessed sodium intake in samples from a generally young adult population (defined as participants aged 25-49, 12 35-54, 26 24-64, 13 19-31, 14 18-34, 15 and 20-36 16 years, respectively). The remaining six studies (33%) did not specify an age group or generally included adults.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation